Islamic economic development in Indonesian Islamic higher education - Hamzah Hamzah; Agus Yudiawan; St. Umrah; Hasbullah Hasbullah (Institute of Advanced Engineering and Science, 2020)
This study aims to explore how changes in community preferences, shari’ah economic development through the tridharma of higher education and its contribution to the development of shari’ah economics. This study was conducted at the UIN Alauddin Makassar, South Sulawesi, Indonesia. This study applied library research. Data collection techniques in this study using discourse from books, articles, magazines, journals, and web (internet). Furthermore, the data were analyzed using the Miles and Huberman model, among others, data reduction, data display and conclusion. The results show that there is a change in community preferences caused by external factors (changes in the social and economic environment) and internal factors in higher education in responding to community dynamics. Higher education can be used as a vehicle in the development of shari’ah Economy through the application of higher education tridharma. Furthermore, higher education also takes a significant role in developing scientific aspects and human resources in the field of Sharia Economics in Indonesia.